Pengembangan media pembelajaran berbasis komputer pada Mata Kuliah Aplikasi Komputer Terapan Tata Busana - Hamidah Suryani; Irmayanti Irmayanti (Seminar Nasional LP2M UNM, 2019)
This paper aims to develop a computer-based learning media for fashion study program in Applied Computer course, investigate the development stages, as well as knowing the feasibility and acceptance level of the developed learning media. This research and development study adopted ADDIE model and modified it into five stages (analysis, design, development, implementation, and evaluation). The result of this study shows that the process of developing computer-based learning media follows the ADDIE model: (a) analyze the curriculum, materials, students, homework, and learning objectives; (b) design the module, learning media, lesson plan, and validation instruments for media, materials and try-out; (c) develop the blueprint and supporting documents; (d) implement and evaluated the developed learning media by experts in learning media and materials, through small group evaluation and field tests. The result of the first evaluation then used to revise the computer-based learning media; (e) in evaluation stage the researchers did not up to this stage to shorten the research cycle. Based on the evaluation by the experts, the developed learning media is feasible and appropriate as the supplementary media for Applied Computer for Fashion Study course in Home Economics Department Faculty of Engineering, Universitas Negeri Makassar